NEW DIAGNOSTIC POSSIBILITIES AND TRADITIONAL POSITIONS IN MODERN ONCOLOGY - Анатолий Агванович Чимитов; Лувсанням Лхагва; Александр Федорович Лазарев; Георгий Цыренович Дамбаев; Тамара Дмитриевна Ханхашанова (Медицина в Кузбассе)
The article presents the results of our own research on the detection of circulating tumor cells in venous blood in 211 cancer patients and 173 donors from the control group. To carry out hemofiltrocytological research, the authors used a special device created for this purpose, and developed a technique and technology for isolating circulating tumor cells. The device and method for determining circulating tumor cells received patents for invention, registered in the State Register. The results of hemofiltrocytological determination of circulating tumor cells were rechecked by the immunofluorescence method in the same cancer patients.